INFLUÊNCIA DO pH DA ÁGUA NA HEPATO E NEFROTOXICIDADE NA INTOXICAÇÃO CRÔNICA POR CÁDMIO EM RATOS WISTAR - Bonfim, Daniel José Pimentel (2014)
Introduction: Cadmium is a heavy metal found in the environment and used industrially and can cause hepato-and nephrotoxic effects. Objective: To evaluate the effect of pH of drinking water in the hepato-and nephrotoxicity caused by chronic cadmium poisoning. Methods: We used 90 Wistar albino rats, adult, male, divided into 6 groups (n = 15): GC5 - solution of cadmium chloride in drinking water at acidic pH (pH 5.0) water; GC7 - solution of cadmium chloride (400mg / L) in drinking water at neutral pH (pH 7.0 water); GC8 - solution of cadmium chloride in water at alkaline pH (pH 8.0); GWC5 - drinking water at acidic pH (pH 5.0); GWC7 - drinking water at neutral pH (pH 7.0); GWC8 - drinking water at alkaline pH (pH 8.0). The animals were euthanized six months after the begnning of the experiment. We performed tests of hepatic and renal function and liver and renal histopathology. Results: The acid pH of the water caused alteration in ALP, ALT and urea in animals exposed to cadmium (p <0.05). In the liver, most of the animals of group GC7 (57.1%) and GC5 group (53.3%) showed diffuse microvesicular steatosis and most of the animals from the other groups showed no steatosis (p> 0.05). In the kidney, although most animals of GC7 group (78.6%) and GWC5 group (71.4%) has presented tubular hydropic degeneration, there was statistically significant difference only in relation to GWC7 group (p <0.05). Conclusion: The cadmium in acid pH of the water led to higher elevation in serum ALP, AST and urea, showing that this heavy metal in a drinking water at acidic pH increases its hepato and nephrotoxic effect.